1) {2х + у = 3
{3х - у = 7
- - - - - - - -
{5х = 10
{у = 3х - 7
- - - - - - - -
х = 10 : 5 у = 3 · 2 - 7 или 2 · 2 + у = 3
х = 2 у = 6 - 7 4 + у = 3
у = -1 у = 3 - 4
у = -1
ответ: (2; -1).
2) {5х + у = 6
{5х + 9у = 14
- - - - - - - - - -
9у - у = 14 - 6 5х + 1 = 6 или 5х + 9 · 1 = 14
8у = 8 5х = 6 - 1 5х = 14 - 9
у = 8 : 8 5х = 5 5х = 5
у = 1 х = 5 : 5 х = 5 : 5
х = 1 х = 1
ответ: (1; 1).
3) {7х + 2у = 3 | доп. множ. 3
{4х + 3у = -2 | доп. множ. (-2)
- - - - - - - - - -
{21х + 6у = 9
{-8х - 6у = 4
- - - - - - - - - -
13х = 13 21 · 1 + 6у = 9 или -8 · 1 - 6у = 4
х = 13 : 13 6у = 9 - 21 6у = -8 - 4
х = 1 6у = -12 6у = -12
у = -12 : 6 у = -12 : 6
у = -2 у = -2
ответ: (1; -2).